Les mutations récentes du foncier et des agricultures en Europe - Chouquer, Gérard; Maurel, Marie-Claude (Les Cahiers de la MSHE Ledoux, 2018)
The book provides an overview of the most recent developments in land and agriculture in Europe. The first part characterizes the evolutions and revolutions of agricultural policies, studied from the point of view of law, political science, agronomy and geography, with an emphasis on the end of a protectionist phase, and with two regional perspectives, one in the Mediterranean and the other in central Europe. A second part examines agricultural and land tenure models: family farming, firm farming, seasonal work, changes in ownership and the evolution towards land portability.